Penggunaan Aplikasi Youtube Sebagai Media Pembelajaran di Madrasah Ibtidaiyah Makassar - Zulhijrah; Andi Prastowo (JKPD (Jurnal Kajian Pendidikan Dasar), 2024)
Using Youtube as a Learning Media in Madrasah Ibtidaiyah Makassar. This study aims to determine the effectiveness of learning by using YouTube as a tutorial-based learning media. The research was conducted in class III at a school in Makassar with 25 students. The research used is a type of research using a qualitative approach. Data collection techniques using techniques, interviews and documentation. The data analysis technique used is data reduction, data presentation, and drawing conclusions. The results of the study show that the effectiveness of YouTube media in learning the tutorial model is quite effective and well implemented, by using YouTube media as a teaching aid for conveying learning material, the use of YouTube media as a tutorial model taught by teachers runs effectively and motivates students to be more active in learning. learning process and achieve optimal learning outcomes. The impact of using YouTube media on students includes being able to increase knowledge, can increase student learning motivation, use of increasingly modern learning media. The research implications of using YouTube as an effective learning medium in increasing student activity in learning.